HARDINESS, HARGA DIRI, DUKUNGAN SOSIAL DAN DEPRESI PADA REMAJA PENYINTAS BENCANA DI YOGYAKARTA - Retnowati, Sofia; Munawaroh, Siti Mukadimatul (Universitas Ahmad Dahlan, 2009)
The purpose of this research was to find out the correlations between hardiness, self-esteem and social support with depression at adolescence survivor of earthquake in Yogyakarta. The population of this research are students of the Yunior High School. The sample was students of the Yunior High School 2 Bantul Yogyakarta. The subject were 149 students, age between 13 - 15 years old. Research employed convenience sampling technique. The data were collected by means of Hardiness Scale, Self-esteem Scale, Sosial Support Scale, and Beck Depression Inventory. The data were analyzed by using multiply regression and partial correlation with SPSS version 12.0 for Windows. The research results were as follows there was a significant correlation between hardiness, self-esteem and social support with depression (R = 0.418, p < 0.05), with contribution (R Square) = 17.5 %, there wasn´t a significant correlation between hardiness and depression (r = 0.01, p > 0.05), there was a very significant and negative correlation between self esteem and depression (r = - 0.289, p <0.01), there wasn´t a significant and positive correlation between social support and depression (r = 0.072, p > 0.05)